THE ORPHANS OF CONSTRUCTIVISM - Longo Mortatti, Maria do Rosario [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
In Brazil, the relationship between the need to overcome social, political and educational problems generated by the military dictatorship established in 1964 and the search for didactic-pedagogical responses to the problems of literacy and illiteracy found its synthesis in the constructivist theory resulting from research by Emilia Ferreiro and presented by her as a conceptual revolution in literacy. Initially, this theory was characterized as counter hegemonic in the set of ideas and practices of leftist, and its disseminators presented it as a promise of overcoming political and didactic-pedagogical problems for the literacy of the popular classes and sons of illiteracy. In the last three decades, however, this theory has consolidated itself as hegemonic (and not only for literacy and public school), having founded, through Brazilian appropriations, a new tradition that identifies the fourth crucial moment (still current) in the history of literacy in Brazil. And nowadays one can evaluate that the introduction and consolidation of constructivism as a theoretical foundation of educational policies contributed, as a disservice, to create generations of orphans of constructivism.
Keywords: Literacy; Constructivism; History of literacy; Brazil